Unlocking high-frequency word mastery: the application of formative assessment in English vocabulary instruction - Prasetyo, Dwi Yoga (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
In terms of foreign language learning, the role of vocabulary mastery is crucial for understanding course materials. However, some students still struggle with mastering English vocabulary, so formative assessment is implemented to explore students’ mastery of high-frequency words (HFWs). Thus, the aim of this research is to investigate the implementation and challenges of employing formative assessment in the learning process for students’ English vocabulary mastery on HFWs. The researcher used the descriptive case study method by conducting a semi-structured interview and observation to collect the data. One class of twelfth graders in this high school was used as the object of observation, and the English teacher and four students were recruited as interview participants. The results of the study showed that variations in formative assessment and providing feedback needed to be considered in the implementation of formative assessment for HFW mastery because all two were continuous in the success of formative assessment. Meanwhile, there were several challenges that arose when carrying out the implementation, such as time constraints, differences in student abilities, and student engagement, each of which is interrelated. These findings can improve teaching practices, emphasize the importance of formative assessment variations, feedback, and contextual HFW instruction.